Implementasi E-RKAM dalam Meningkatkan Efektivitas Pengelolaan Keuangan Madrasah: Studi Kasus di MIM Kedungjampang, Purbalingga - Imam Nisfusofar; Umu Latifah; Wahyu Septiani; Sudiro Sudiro; Muh. Hanif (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of the Electronic Madrasah Work and Budget Plan (E-RKAM) in improving the effectiveness of financial governance at MI Muhammadiyah Kedungjampang, Purbalingga. The focus of this research includes the implementation process of E-RKAM, supporting and inhibiting factors, and its contribution to the effectiveness of madrasah financial governance. This study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the treasurer, the head of the madrasah, and other parties related to financial management. Data analysis was conducted using the interactive analysis model proposed by Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of E-RKAM was carried out systematically and integratively through the stages of planning, disbursement, realization, and accountability reporting assistance. Supporting factors include the availability of supporting facilities, E-RKAM training, and effective communication among madrasah administrators. Meanwhile, the inhibiting factors include network and server disruptions as well as the complexity of data input procedures. The implementation of E-RKAM contributed positively to the effectiveness of madrasah financial governance by improving budgeting efficiency, strengthening financial control, and enhancing transparency and accountability in financial management.